Effect of maturation periods and leukaemia inhibitory factor on in vitro bovine embryo development - Margawati, Endang Tri (Indonesian Journal of Animal and Veterinary Sciences, 1995)
The period of in vitro maturation,~20 vs 24 hours) with of without supplementation of :,~uk_ni;ia inhib toryy factor (LIF) (0, 500, 1000 or 2000 U/ml) was studied on bovine embryo development in vitro in a 2 x 4 factotial experiment w id oestgnoo i, a randomized block design . A total of 870 bovine oocytes were used . Besides embryo development, cell numbers of blastocysts v. : ;re also co , mted in order to study the quality of the embryos . Oocytes were matured in a modified TCM199 medium containing 10 ug/nil of FS-14 and LP., I 1~ t1L rstradiol, fertilized in TALP and cultured in SOF/AABSA medium. There was no interaction between maturation periods and LIF doses on embryo development (P>0 .05). Maturation periods, however, affected (P<0.05) blastocyst rates but did not for cleavage o, oocytes and the percentage of oocytes that developed into blastocysts . LIF doses during in vitro maturation did not affect embryo development (P>0 .05) . Cell numbers of blastocysts were also not affected by maturation periods and LIF doses (P<0 .05), however 20 h in vitro maturation and supplementation of LIF doses tended to increase the cell numbers. This study suggests that 20 h maturation increases blastocyst rates and that supplementation with LIF during maturation does not affect the quality of embryos produced in vitro. Key words : in vitro fertilization, oocyte, cleavage, blastocyst, cell numbers of blastocyst